Qal'at Jabar Pottery A Study of a Syrian Fortified Site in the Late 11th-14th Centuries - Tonghini, Cristina (Council for British Research in the Levant, 1998)
By studying both the archaeological evidence and the written records, this volume provides a new means of interpreting and reconstructing the history of an important fortified site of the middle Euphrates valley, Qalat Jabar, and clarifies its connection with the neighbouring regions. A detailed classification of the pottery finds from the late eleventh to the fourteenth centuries provides a chronological framework for the major changes in ceramic production - a valuable model which can be used for other sites. This is an example of the detailed archaeological research that has greatly advanced our understanding of the history of the Euphrates valley in the Middle Ages.